Speciation and Bio-Imaging of Chromium in Taraxacum officinale Using HPLC Post-column ID-ICP-MS, High Resolution MS and Laser Ablation ICP-MS Techniques - Marković, Stefan; Levstek, Lucija; Žigon, Dušan; Ščančar, Janez; Milačič, Radmila (Frontiers in Chemistry, 2022)
A new analytical procedure for the speciation of chromium (Cr) in plants by high performance liquid chromatography inductively coupled plasma mass spectrometry (HPLC-ICP-MS) was developed using a strong anion-exchange Mono Q column for the separation of the Cr species. To optimize the analytical procedure, Cr complexes were first synthesized from Cr-nitrate with the addition of an excess of ligand (90 °C). Cr-oxalate, Cr-malate, Cr-citrate, Cr-aconitate and Cr-quinate complexes and Cr-nitrate (pH 6.5) were chromatographically separated from Cr(VI) by applying linear gradient elution from 100% water to 100% NH4Cl at a flow rate of 1.5 mL min-1 in 10 min. The column recoveries ranged from 100 to 104%. The exception was Cr-aconitate (column recovery 33%), where a quantitative synthesis was not possible. Good repeatability of the measurements (relative standard deviations better than ± 3%) and low limits of detection (below 0.37 ng mL-1 Cr) were achieved for the individual Cr species. The developed analytical procedure was applied to Cr speciation for dandelions (Taraxacum officinale) grown in soil with a high Cr content and a study of the uptake and metabolism of Cr species in dandelions grown in soil with a low Cr content treated with solutions of Cr(VI) or Cr-nitrate (5000 ng mL-1 Cr, pH 6.5) for 48 h. The separated Cr species were quantified by post-column isotope dilution ICP-MS, while the identification was based on retention times and was also supported by mass spectra obtained with high resolution mass spectrometry (HR-MS). The data indicate that for dandelions grown in Cr-rich soil and that treated with Cr-nitrate (pH 6.5), the Cr was mainly accumulated in the roots, while in plants treated with Cr(VI) (pH 6.5), the Cr was evenly distributed between the roots and the leaves. The Cr species found in dandelion roots and leaves were Cr-aconitate, Cr-malate and Cr-quinate. The results revealed that Cr(VI) was completely reduced and metabolized to Cr(III) complexes. LA-ICP-MS data showed that the Cr in a leaf of dandelion grown in Cr-rich soil was localized mainly at the apex of the leaf.